RETHINKING POLITIK PENDIDIKAN ISLAM DI INDONESIA - Choirul Mahfud (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
In Indonesia, education and politics have a close connection and inter-dependant. Many educational policies in this country have been issued through political decision. Furthermore, many teachers have been produced political elites and bureaucrat s. Sometimes, different ministry means different policy. Furthermore, the existence of Islamic education in Indonesia cannot be separated from political policies before the independence era until now. Therefore, this article asks: what does the politics of Islamic education mean? Is there any relation between politics and Islamic education? What are kind of political Islamic education policy products? Why does the political dichotomy between Islamic education and secular education always happen? Where can the political policy of Islamic education in Indonesia be brought? The research of this article is descriptive-qualitative. The data are taken from many sources such as library, documentation, and mass-media.